Results of conjunctival autograft transplantation combined with amniotic membrane transplantation surgery in recurrent pterygium cases - Tanrıverdi, Cafer; Balcı, Özlem (Alanya Alaaddin Keykubat University, 2021)
Aim: To evaluate the results of conjunctival autograft transplantation (CAT) combined with amniotic membrane transplantation (AMT) surgery in recurrent pterygium cases.Methods: This is a retrospective interventional case series involving patients admitted to our clinic with recurrent pterygium. Patients' examination and postoperative findings were taken through standard slit-lamp examinations. Fourteen eyes of 14 patients were included in the study. All cases were treated with excision, followed by CAT combined with AMT. Corneal recurrence was evaluated as the main result. Fibrovascular proliferation greater than 1 mm on the cornea was accepted as recurrence after surgery.Results: The mean age of patients was 56.4 ± 7.5 (range: 40 – 65) years. During the mean follow-up period of 24.9 ± 10.7 (range: 12 – 50) months, pterygium and symblepharon recurred in only one eye (7.1%) after 4 months.Conclusion: In this study, it was seen that acceptable results were obtain and low recurrence rates could be achieved with the combination of CAT and AMT for the treatment of recurrent pterygium.

Amaç: Tekrarlayan pterjiumlu olguların tedavisinde konjonktival otogreft transplantasyonu (KOT) ile kombine amniyotik membran transplantasyonu (AMT) sonuçlarını değerlendirmekMetot: Bu çalışma kliniğimize tekrarlayan pterjiyum ile başvuran hastaları içeren retrospektif girişimsel bir vaka serisidir. Hastaların muayeneleri ve postoperatif bulgular standart yarık lamba biomikroskopi ile yapıldı. Çalışmaya 14 hastanın 14 gözü alındı. Tüm olgularda pterjium eksizyonunu takiben KOT ile kombine AMT yapıldı. Ana sonuç olarak korneal nüks değerlendirildi. Kornea üzerinde 1 mm'den fazla fibrovasküler proliferasyon ameliyat sonrası rekürrens olarak kabul edildi.Bulgular: Hastaların ortalama yaşı 56.4 ± 7.5 (aralık: 40- 65) yıldı. Ortalama 24.9 ± 10.7 (aralık: 12- 50) aylık takip süresi sonunda sadece bir gözde (% 7.1) 4 ay sonra pterjium ve symblepharon tekrarladı.Sonuç: Bu çalışmada, tekrarlayan pterjium tedavisi için KOT ve AMT kombinasyonu ile kabul edilebilir sonuçlar alındığı ve düşük nüks oranları sağlanabileceği görüldü.
Tekrarlayan pterjiyumlu olgularda konjonktival otogreft transplantasyonu ile kombine amniyotik membran transplantasyonu cerrahisi sonuçları
Keywords: Pterygium; Conjunctival Diseases; Amnion; Cornea; Pterjium; Konjonktival Hastalıklar; Amnion; Cornea